Neurocutaneous syndromes in art and antiquities. Issue 2 (20th May 2021) - Ruggieri, Martino; Gentile, Amalia Egle; Ferrara, Vincenza; Papi, Massimo; Praticò, Andrea D.; Mudry, Albert; Taruscio, Domenica; Micali, Giuseppe; Polizzi, Agata
Abstract: Neurocutaneous syndromes are a group of genetic disorders affecting the skin, the central and peripheral nervous system, and the eye with congenital abnormalities and/or tumors. Manifestations may also involve the heart, vessels, lungs, kidneys, endocrine glands and bones. When people with these disorders are portrayed in works of art, physicians have speculated on possible diagnoses. In particular, many figures have been labeled as possibly having a neurocutaneous disorder, sometimes distorting the popular conception of these diseases. We review numerous documents, drawings, prints, lithographs, xylographs, and portraits which span the ages from antiquity to the era of the pioneers behind the eponyms, depicting a large spectrum of neurocutaneous disorders.